Ethno-STEM-Integrated Enriched Chemistry Book to Equip Chemical and Numeracy Literacy - Amroeni Rosyada; Woro Sumarni; Murbangun Nuswowati; Ade Noorliza Niyamae (Journal of Innovation in Educational and Cultural Research, 2025)
Students in Indonesia face chemical literacy and numeracy challenges, which are essential for understanding scientific concepts and solving real-world problems. Ethno-STEM offers a promising approach by helping students learn through contextualized problems. This study aims to develop enrichment books integrating Etno-STEM, focusing on typical Pati Regency foods, to enhance students' chemical literacy and numeracy. Using the RD method with the 4D model, the study involved grade XI and XII students from SMAN 2 Pati and SMAN 1 Tayu. Validation by experts and trials confirmed the book's quality, with the Rasch model validating its content and assessments. The results show that (1) the developed enrichment book has 12 characteristics, (2) it was validated as a high-quality enrichment resource, and (3) it received positive feedback from teachers and students, demonstrating its potential to improve chemical literacy and numeracy while fostering cultural appreciation. This study provides a practical solution to improving students' chemical literacy and numeracy through Ethno-STEM integration, offering a culturally relevant resource that supports the goals of the Merdeka Curriculum and promotes appreciation of local cultural wisdom.